The Protestant landscape of the Tyumen Region: locations, size, and demographic composition of urban church meetings - Poplavsky R.O.; Cherepanov M.S.; Bobrov I.V.; Shisheliakina A.L. (Вестник археологии, антропологии и этнографии, 2022)
Modern sociological studies of Protestantism are focused mainly on how communities are formed and develop in the context of their relations with the state and between themselves, personal stories of the believers, and contents and forms of conducting religious practices. Researchers often neglect to describe the numbers and demographic characteristics of practicing believers, and to analyze changes of these parameters over time. In this paper, based on the materials of the field research conducted in Tyumen, Tobolsk, Ishim, and Yalutorovsk in 2014–2016, we identify the locations, demographic composition, and size dynamics of the Protestant prayer meetings. The paper showcases new data on Tyumen accounting for the associations which appeared after 2011 and for the first time presents materials on Tobolsk, Ishim, and Yalutorovsk. Non-participant structured observation was the principal method of the field research. Analysis of photographic documents posted on the web-sites and web-pages of the Protestant associations, as well as interviews with religious specialists were used as additional methods. We observed that there was an increase in the number of Protestant associations from 2008 to 2016: the number of the associations in Tyumen increased by five and about five new communes appeared in the other cities. The most attended weekly prayer meetings were recorded in Tyumen in 2016. They gathered up to 200 people. The largest services in Ishim and Yalutorovsk in 2015 were attended by up to 70 people. The communal prayers in Tobolsk in 2014 were attended by up to 170 people. We have identified the following factors that influence the size of the prayer meetings: ownership of the premises by the association and the period of its activity in the region. Communes who have their own premises are larger than those renting an office or a building of another Protestant association. Also, churches formed in the early or mid-1990s feature the largest numbers of the parishioners. It was found that in all studied cities middle-aged women represent the largest group of the parishioners, which is consistent with the results of research in other Russian cities and towns.